Innovation Strategies for Cultural Heritage Revitalization: A Digital Technology-Driven Approach in Hohhot’s “Museum City” - Wang, Ni (Pacific International Journal, 2025)
In this paper, we consider how the digital revives our cultural heritage, through mixed-methods case study of Hohhot’s “Museum City”, exploring with the theories of “digital authenticity” and “participatory heritage”, in terms of its immersive VR reconstructions, and with AI multilingual interpretation systems, and its IoT-based environment supervision.Through our experimental results, we achieve a low-cost AR/VR-based hybrid model with an adopted sense-of-place that has a positive impact by bringing tourism revenue growth at 35%(2021-2023). It tackles potential harms (such as an AI-simplified depiction of the minorities’ history) under policy recommendations that favor inclusive and multistakeholder governance while being consistent with China’s policy aim of being a ”Digital China” and providing opportunities for communities to thrive in non-coastal areas of China.